Urinary NGAL and RBP Are Biomarkers of Normoalbuminuric Renal Insufficiency in Type 2 Diabetes Mellitus - Aimei Li; Bin Yi; Yan Liu; Jianwen Wang; Qing Dai; Yuxi Huang; Yan Chun Li; Hao Zhang (Journal of Immunology Research)
Objectives. As a screening index of diabetic kidney disease (DKD), urinary albumin/creatine ratio (UACR) is commonly used. However, approximately 23.3%-56.6% of DKD patients with estimated glomerular filtration rate eGFR<60 ml/min per 1.73 m2 are normoalbuminuric. Thus, urinary biomarkers of nonalbuminuric renal insufficiency in type 2 diabetes mellitus (T2DM) patients are urgently needed. Methods. This cross-sectional study enrolled 209 T2DM patients with normoalbuminuria whose diabetes duration was more than 5 years. The patients were classified into two groups, NO-CKD (eGFR≥60 ml/min per 1.73 m2, n=165) and NA-DKD (eGFR<60 ml/min per 1.73 m2, n=44). Levels of urinary neutrophil gelatinase-associated lipocalin (NGAL), retinol-binding protein (RBP), plasminogen activator inhibitor-1 (PAI-1), vascular cell adhesion molecule-1 (VCAM-1), and E-cadherin were detected, and their correlations with eGFR, plasma TNF-α, IL-6, endothelin-1 (ET-1), and 8-hydroxydeoxyguanosine (8-OHdG) were assessed. Results. Among patients with renal insufficiency, 26.0% was normoalbuminuric. Compared to the NO-CKD group, the NA-DKD group was older with lower hemoglobin (HB) levels and higher systolic blood pressure (SBP), plasma TNF-α, IL-6, and 8-OHdG levels. Logistic regression analysis suggested that age, TNF-α, and 8-OHdG were independent risk factors for nonalbuminuric renal insufficiency. Compared to the NO-CKD group, the NA-DKD group exhibited significant increases in urinary NGAL and RBP levels but not PAI-1, VCAM-1, and E-cadherin. Urinary NGAL and RBP both correlated negatively with eGFR and positively with plasma IL-6 and 8-OHdG. Multiple linear regression indicated NGAL (β=−0.287, p=0.008) and RBP (β=−44.545, p<0.001) were independently correlated with eGFR. Conclusion. Age, plasma TNF-α, and 8-OHdG are independent risk factors for renal insufficiency in T2DM patients with normoalbuminuria. Urinary NGAL and RBP can serve as noninvasive biomarkers of normoalbuminuric renal insufficiency in T2DM.